Four decades of health education in the Philippine public schools 1900-1940 - Clemente, Ursula Uichanco (Education quarterly.)
The development of health education in the public schools in its various aspects was traced from the start of the school system to the late thirties. Health services (medical, dental, nursing), health instruction, health inspection and examination, health supervision, teacher training, health facilities, and public health education were treated in that order. It was shown that. In all these health work, almost all health agencies cooperated: the United States Commission of Public Health, the Philippine Health Service, the American Red Cross, the Public Welfare Commission, the Junior Red Cross, the Anti-Tuberculosis Society.